Transforming sustainable and green supply chains with artificial intelligence: A strategic review and future research opportunities - S. Porkodi; V.V. Phani Kumar Tantravahi; Bassam Khalil Hamdan Tabash (International Journal of Production Management and Engineering, 2025)
Supply chain management (SCM) using artificial intelligence (AI) transforms business practices by encouraging sustainability. Gaining insight into AI's role in improving supply chain effectiveness and lowering environmental impact is essential as demand for sustainable practices rises. This study aims to investigate how AI contributes to sustainability in SCM and determine the primary challenges and opportunities associated with implementing AI. The study aims to provide an extensive review of AI's potential to assist sustainable and green supply chain practices. This standard and strategic literature review was conducted employing the Scopus database. The five-stage methodology was adopted in the review process, which includes pilot search, locating studies, study selection, synthesis analysis, and reporting. The choice of 82 relevant studies on AI and sustainable SCM was made during the review after the exclusion of irrelevant articles. The review emphasises AI's significant role in enhancing sustainability in SCM by reducing environmental impact, improving resource efficiency, and promoting green practices. However, the study also highlights the identification of challenges such as integration complexity, implementation cost, and technological limitations and future agenda.